3(x-4)+14=47
giúp e
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3\cdot\left[\left(4-x\right)3+51\right]\div3-2^2=14\)
\(\Rightarrow3\cdot\left(12-3x+51\right)\div3-4=14\)
\(\Rightarrow3\cdot\left(-3x+12+51\right)\div3=14+4\)
\(\Rightarrow3\cdot\left(-3x+63\right)\div3=18\)
\(\Rightarrow-9x+189=18\cdot3\)
\(\Rightarrow-9x+189=54\)
\(\Rightarrow-9x=54-189\)
\(\Rightarrow-9x=-135\)
\(\Rightarrow x=15\)
3.( (4-\(x\)).3 + 51) : 3 - 22 = 14
(3:3).( (4- \(x\)).3 + 51) - 4 = 14
(4- \(x\)).3 + 51 = 14 + 4
( 4 - \(x\)).3 + 51 = 18
( 4 - \(x\)). 3 = 18 - 51
( 4 - \(x\)).3 = - 33
4 - \(x\) = - 33 : 3
4 - \(x\) = -11
\(x\) = 4 - (-11)
\(x\) = 15
a: \(=\dfrac{2\left(x+2\right)\left(x-1\right)}{x+2}=2x-2\)
b: \(=\dfrac{2x^3+x^2-6x^2-3x+2x+1}{2x+1}=x^2-3x+1\)
c: \(=\dfrac{x^3+2x^2-2x^2-4x+2x+4}{x+2}=x^2-2x+2\)
d: \(=\dfrac{x^2\left(x-3\right)}{x-3}=x^2\)
d) 3 -x = |-4|
3-x=4
x=-1
e) 35 - |2 x+1|=14
|2 x+1|=21
\(\Leftrightarrow\orbr{\begin{cases}2x+1=21\\2x+1=-21\end{cases}\Leftrightarrow\orbr{\begin{cases}x=10\\x=-11\end{cases}}}\)
f) |x| -3 +6 =16
|x|=13
\(x=\pm13\)
P/s tham khảo nha
d)=>3-x=4
=>x=3-4
=>x=-1
vậy x=-1
e)=>l2x+1l=35-14=21
=>\(\orbr{\begin{cases}2x+1=21\\2x+1=-21\end{cases}\Leftrightarrow\orbr{\begin{cases}2x=21-1=20\\2x=-21-1=-22\end{cases}\Leftrightarrow\orbr{\begin{cases}x=20:2=10\\x=-22:2=-11\end{cases}}}.}\)
vậy x=10,x=-11
f)=>lxl=16-6+3=13
\(\Rightarrow x=\pm13\)
vậy..............
\(a,2.\left(x-5\right)-3.\left(x+7\right)=14\)
\(2x-10-3x-21=14\)
\(-x-31=14\)
\(x=-31-14\)
\(x=-45\)
\(b,5.\left(x-6\right)-2\left(x+3\right)=12\)
\(5x-30-2x-6=12\)
\(3x-36=12\)
\(3x=12+36\)
\(3x=48\)
\(x=16\)
\(c,-5.\left(2-x\right)+4.\left(x-3\right)=10.x-15\)
\(-10+5x+4x-12=10x-15\)
\(-6x-22=10x-15\)
\(-6x-10x=-15+22\)
\(-16x=7\)
\(x=-\frac{7}{16}\)
Câu d , e f tương tự nha
a) \(...\Rightarrow x.\left(2+5\right)=14\Rightarrow x.7=14\Rightarrow x=14:7=2\)
b) \(...\Rightarrow x.\left(9+1\right)=20\Rightarrow x.10=20\Rightarrow x=20:10=2\)
c) \(...\Rightarrow x.\left(\dfrac{2}{3}+\dfrac{1}{3}\right)=1999\Rightarrow x.\dfrac{3}{3}=1999\Rightarrow x=1999\)
d) \(...\Rightarrow11.x+22=5.x+40\Rightarrow11.x-5.x=40-22\Rightarrow6.x=18\Rightarrow x=18:6=3\)
e) \(...\Rightarrow11.x-66=4.x+11\Rightarrow11.x-4.x=11+66\Rightarrow7.x=77\Rightarrow x=77:7=11\)
f) \(...\Rightarrow\left(3.x-12\right):x=12-10\)
\(\Rightarrow3.x-12=2.x\)
\(\Rightarrow3.x-2.x=12\)
\(\Rightarrow x=12\)
g) \(...\Rightarrow\left(5.x+7\right):x=26-20\)
\(\Rightarrow5.x+7=6.x\)
\(\Rightarrow6.x-5.x=7\)
\(\Rightarrow x=7\)
h) \(...\Rightarrow x.\left(1999-1\right)=1999.\left(1997+1\right)\)
\(\Rightarrow x.1998=1999.1998\)
\(\Rightarrow x=1999.1998:1998\)
\(\Rightarrow x=1999\)
a, \(x\times\) 2 + \(x\times\) 5 = 14
\(x\) \(\times\) ( 2 + 5) = 14
\(x\) \(\times\) 7 = 14
\(x\) = 14: 7
\(x\) = 2
b, \(x\times9\) + \(x\)= 20
\(x\) \(\times\)( 9 + 1) = 20
\(x\) \(\times\) 10 = 20
\(x\) = 2
c, \(x\) : \(\dfrac{3}{2}\) + \(x\times\dfrac{1}{3}\) = 1999
\(x\times\) \(\dfrac{2}{3}\) + \(x\) \(\times\dfrac{1}{3}\) = 1999
\(x\times\) ( \(\dfrac{2}{3}\) + \(\dfrac{1}{3}\)) = 1999
\(x\) = 1999
d, 11\(\times\)(\(x+2\)) = 5 \(\times\) \(x\) + 40
11 \(\times\) \(x\) + 22 = 5 \(\times\) \(x\) + 40
11 \(\times\) \(x\) = 5 \(\times\) \(x\) + 40 - 22
11 \(\times\) \(x\) = 5 \(\times\) \(x\) + 18
11 \(\times\) \(x\) - 5 \(\times\) \(x\) = 18
\(x\) \(\times\) ( 11 - 5) = 18
\(x\) \(\times\) 6 = 18
\(x\) = 3
TL
x=15
HT
đây
3(x - 4) = 47 - 14= 33
x - 4 = 33 : 3 = 11
x = 11 + 4 = 15
Đ/S: 15